Socioeconomic determinants of cumulative fertility in Ghana. - Samuel H Nyarko (PLoS ONE, 2021)
The pace of decline in fertility rates in sub-Saharan Africa appears to have slowed or stalled in the last few decades. This study examines the socioeconomic associated with cumulative fertility in Ghana. Negative binomial regression models were used to estimate determinants of cumulative fertility using data from the Ghana Demographic and Health Surveys of 2003, 2008, and 2014. The composition of children ever born by women did not change considerably over the study periods. Socioeconomic disparities in educational attainment, household wealth, employment, and employer status are significantly associated with cumulative fertility risks in Ghana. The current age of women, age at sexual debut, and marital status, among others, are also linked to cumulative fertility levels. Place and region of residence are also linked to fertility in Ghana. Cumulative fertility levels in Ghana are underscored by considerable socioeconomic disparities among women of reproductive age. Fertility regulation policies should hinge on improving the socio-economic wellbeing of women in Ghana.